A Study on the Relationship between Blood Group and Type of Cancer - Idris, Ehsan M. (Scientific Journal for Faculty of Science-Sirte University, 2022)
The presence and lack of blood antigens in some blood groups induce blood membrane changes, morphologically and functionally, and it is related to some kind of disease such as cancer. Structure-dependent functions of blood types can relate the blood groups to health and diseases. The study aimed to determine the association of "ABO" and "Rhesus" blood groups with the frequency of cancer. A total of 576 cancer patients participated in this study, and they were diagnosed with different types of cancer. The results showed that blood types A and O have a high rate of occurrence of breast cancer and lung cancer, the positive Rhesus blood type has a high incidence of breast cancer. Meanwhile, the Rhesus negative blood type has a high incidence of stomach cancer. In conclusion, this study supports previous studies about the relationship between the blood group type and the probability of cancers occurring.